Ethnographic Research in a Cyber Era. (June 2014) - Hallett, Ronald E.; Barber, Kristen
Ethnographers have long been concerned with how individuals and groups live out life in social spaces. As the Internet increasingly frames lived experiences, researchers need to consider how to integrate data from online spaces into "traditional" ethnographic research. Drawing from two ethnographic studies, we explain how online spaces were needed to more fully understand the physical environments and issues we studied. In addition to discussing how we were led online, we present ethnographic data to demonstrate the epistemological importance of considering online spaces. While traditional methods of ethnography (i.e., in-person observations and informal interviews) continue to be useful, researchers need to reconceptualize space as well as what counts as valuable interactions, and how existing (and new) tools can be used to collect data. We argue that studying a group of people in their "natural habitat" now includes their "online habitat." We conclude with a call for ethnographers to consider how digital spaces inform the study of physical communities and social interactions.